Spectral Line Fitting of an Astronomical Source - Scott C. Jones; David A. Naylor; Brad G. Gom; Locke D. Spencer (Bridging Excellence – The 30$^\mboxth$ Canadian Symposium on Remote Sensing, June 22-25, Lethbridge, Alberta, Canada, 2009)
n/a